For instance, we'll take the function h(x)=sqrt(x^2 + 1)
and we'll have to decompose it into simpler functions:
h(x)
= f(g(x))
We can take g(x) = x^2 + 1 and f(x) = sqrt
x
Now, we'll compose f(x) and g(x) and we'll
get:
h(x) =
(f*g)(x)
(f*g)(x) =
f(g(x))
f(g(x)) = sqrt
g(x)
We'll substitute g(x) = x^2 +
1
h(x) = f(g(x)) = sqrt (x^2 +
1)
We also can take as f(x) = sqrt (x+1)
and g(x) = x^2.
(f*g)(x) =
f(g(x))
We'll substitute the variable x, from the
expression of f(x), by the expression of g(x).
f(g(x)) =
sqrt [g(x) + 1]
h(x) = f(g(x)) = sqrt (x^2+
1)
No comments:
Post a Comment